Brain organoid model systems of neurodegenerative diseases: recent progress and future prospects - Shaikh, Saniyah; Siddique, Luqman; Khalifey, Hafsah T.; Mahereen, Rutaba; Raziq, Thaabit; Firdous, Rushdan M.; Siddique, Aisha; Shakir, Ismail M.; Ahmed, Zara; Akbar, Arshiya; Alshehri, Eman A.; Chinappan, Raja; et al. (Frontiers in Neuroscience, 2025)
Neurological diseases are a leading cause of disability, morbidity, and mortality, affecting 43% of the world’s population. The detailed study of neurological diseases, testing of drugs, and repair of site-specific defects require physiologically relevant models that recapitulate key events and dynamic neurodevelopmental processes in a highly organized fashion. As an evolving technology, self-organizing and self-assembling brain organoids offer the advantage of modeling different stages of brain development in a 3D microenvironment. Herein, we review the utility, advantages, and limitations of the latest breakthroughs in brain organoid endeavors in the context of modeling three of the most prevalent neurodegenerative diseases—Alzheimer’s, Parkinson’s, and Huntington’s disease. We conclude the review with a perspective on the future prospects of brain organoid models with their myriad possible applications in translational medicine.